MENINGKATKAN HASIL BELAJAR SISWA SMP KELAS VIII PADA MATERI PERSAMAAN GARIS LURUS MELALUI PEMBELAJARAN DARING MENGGUNAKAN PENDEKATAN SAINTIFIK BERBANTUAN SOFTWARE GEOGEBRA - Trinuraini Trinuraini; M. Afrilianto (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study intends to examine the improvement of the learning outcomes of middle school students in grade VIII on straight-line equation material. The sample taken by students as many as 40 students of class VIII at SMP Negeri 4 Cimahi. Classroom action research consists of 2 cycles, each cycle consists of 2 meetings. Students are given preliminary tests on straight-line equation materials to find out the initial ability before classroom action research, cycle I and cycle II (after action) tests, and observation sheets for teachers and students. The stages of this research approach include the stages: action planning, execution of actions, observation and assessment, and reflection. The data processing technique in this study is to find the average value using Microsoft Exel. In cycle I with an average value of 78.85 and cycle II with an average value of 90 experienced an increase of 11.15 from the results of cycle I. It was concluded that learning outcomes through online learning using short students in grade VIII straight line equations can be improved by assisting geogebra software.